The Role of Bloom’s Taxonomy in Curriculum Approach - Syarif Hidayat; Zaitun Qamariah (PT. Padang Tekno Corp, 2023)
The background of this study was to examine how big the role of Bloom's taxonomy is in the curriculum approach as a work tool that functions to clarify learning objectives, to develop an education system in a more efficient direction. This research uses the Library Research method, this method was chosen because with the Library Research method researchers can clearly analyze various conceptual information as well as qualitative and quantitative data from previous research. The conclusion obtained is that with the progress of the times, education must also develop and one of the education systems used in learning is the curriculum. With an efficient curriculum and in accordance with the needs of students in his day, the curriculum can be said to have succeeded in achieving its goals. Bloom's Taxonomy is present as a framework to help and also as evaluation material to revise or update the existing curriculum.